Three new species of Harttia (Loricariidae: Loricariinae) from Serra do Cachimbo, Rio Xingu basin, Pará, Northern Brazil - Oyakawa, Osvaldo T.; Fichberg, Ilana; Py-Daniel, Lucia Rapp (Zootaxa, 2018)
Three new species of Harttia from the Rio Xingu basin in the region of Serra do Cachimbo, Pará State, Brazil, are described. Harttia rondoni n. sp., H. panara n. sp. and H. villasboas n. sp. were collected in the Rio Curuá, a tributary of Rio Iriri, Rio Xingu drainage. Harttia rondoni was additionally recorded from the Rio Fresco basin, a tributary of the middle Rio Xingu. The three new species represent the first records for the genus in this drainage. Harttia rondoni differs from H. panara and H. villasboas by having the abdomen partially covered by plates. Harttia panara differs from H. rondoni and H. villasboas by having a larger body depth and interorbital distance. Harttia villasboas differs from H. rondoni and H. panara by having the anterior profile of the head elliptical in dorsal view and a more elongated snout. Additionally, the 26 species of Harttia described are organized in three species group based on the pattern of abdominal covering.